Tracking Student Success : Who is Falling Through the Cracks : Final Report. - von Treuer, Kathryn; Marr, David (Office for Learning and Teaching, 2013)
This final report on Tracking student success looks at : Australian higher education lags behind other western countries in relation to access and attainment of equity groups. The study monitored secondary school leavers during the first five years of their university experience to identify factors that enabled access, retention and success with students from diverse backgrounds. Action learning teams which were formed at Deakin University and Southern Cross University, in parallel, allowed the researchers to compare the role of different settings in shaping the student experience. The first phase of the study focused on developing a methodology or 'tracking system' for monitoring student cohorts from leaving school to exiting the University. They aimed to: make recommendations about the structures (including school partnerships) and the processes and technologies required to enable the tracking of student cohorts. The authors also presented findings of the comparative case study which particularly focused on points of learning across the two institutions that may provide benchmarks for other institutions.